2006
DOI: 10.5511/plantbiotechnology.23.329
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of monofluorophenols by cultured cells of Eucalyptus perriniana

Abstract: On the biotransformation of phenol and monofluorophenols by the cultured cells of Eucalyptus perriniana, phenyl and fluorophenyl b-D-glucosides were isolated after a 1-h incubation. Especially, the yield of 2-fluorophenol is higher than those of the other substrates, i.e., phenol, 3-and 4-fluorophenols. These results indicated that E. perriniana cells selectively glycosylate the hydroxyl group of 2-fluorophenol discriminating phenol, 3-and 4-fluorophenols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…americana cells were subcultured at four-week intervals for two months on solid Murashige and Skoog medium (MS; 100 mL in a 300-mL conical flask) containing 3% sucrose, 10 mM 2,4-dichlorophenoxyacetic acid, and 1% agar (adjusted to pH 5.7) at 25°C. [23][24][25][26][27][28][29] A suspension culture was started by transferring the cultured cells to 100 mL of liquid medium in a 300-mL conical flask, and incubated on a rotary shaker (120 rpm) at 25°C. Prior to use in this work, some of the callus tissue (fresh weight (fr.…”
Section: Analysesmentioning
confidence: 99%
“…americana cells were subcultured at four-week intervals for two months on solid Murashige and Skoog medium (MS; 100 mL in a 300-mL conical flask) containing 3% sucrose, 10 mM 2,4-dichlorophenoxyacetic acid, and 1% agar (adjusted to pH 5.7) at 25°C. [23][24][25][26][27][28][29] A suspension culture was started by transferring the cultured cells to 100 mL of liquid medium in a 300-mL conical flask, and incubated on a rotary shaker (120 rpm) at 25°C. Prior to use in this work, some of the callus tissue (fresh weight (fr.…”
Section: Analysesmentioning
confidence: 99%
“…HPLC analyses of the control cell cultures of N. tabacum , which had not been treated with 2-, 3-, and 4-fluorophenols ( 1 , 4 , and 6 ), showed that there were no mono-fluorophenols and their glycosides in both medium and N. tabacum cells. On the basis of the spectroscopic analyses such as FABMS, 1 H- and 13 C-NMR, the chemical structures of the products were determined to be 2-fluorophenyl β-glucoside ( 2 , 60%) [ 16 ] and 2-fluorophenyl β-gentiobioside ( 3 , 10%) of which 3 has not been identified before.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that cultured Eucalyptus perriniana cells converted 2-, 3-, and 4-fluorophenols into the corresponding β-glucosides [ 16 ]. On the other hand, it has been reported that exogenously added α-tocopherol was glycosylated to its β-gentiobioside by N. tabacum cell cultures [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The yield of 11, only 16% from substrate 2, without chlorination at C-6 confirmed this speculation. This phenomenon has also been observed for the glycosylation of monofluorophenols by cultured cells of Eucalyptus perriniana, 16) The autoxidative activity of the products as determined by the 2,2 0 -diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method showed that the IC 50 values of 15 (491 mM) and 16 (606 mM) were much lower than those of compounds 6 and 7 (which were both higher than 1000 mM). On the other hand, the glycosylation of compound 8 (110 mM) reduced its antioxidant activity dramatically.…”
mentioning
confidence: 95%
“…The corresponding glycosides (10-18), involving four new compounds (15)(16)(17)(18), were biosynthesized by the hairy roots (see Fig. 1).…”
mentioning
confidence: 99%